靶向肽在递送siRNA进行肺癌治疗研究中的应用 (Zhongguo Fei Ai Za Zhi, 2014)
Lung cancer is considered a kind of malignant tumors of the world highest incidence. As it is not sensitive to chemotherapy and easy to produce drug resistance, improving effect of anticancer drug becomes a research focus recent years. siRNA, small interfering RNA, can silence complemenary mRNA which is a kind of gene therapy. Target peptides are small molecular peptides which specifcally bind to tumor surface materials. When used with siRNA, target peptides can increase accumulation of siRNA in tumor cells and enhance the silencing effect. As result, drug resistance of lung cancer reduced and the effect of therapy can be improved. Tis method provides new direction and strategy for targeted therapy of lung cancer. Tis article will make a brief overview of target peptides applying in siRNA dilivery for the research of lung cancer treatment.